Alternative signification exploring the use of semiotics to teach critical thinking/reading - Miciano, Remedios Z. (2004)
Three classes in Developmental Reading were surveyed twice to explore the effectiveness of using alternative signification, a reading strategy based on semiotics, in teaching critical thinking/ reading. The first survey administered before the exercise on alternative signification was used to determine the students' reading of a Chivas Regal ad. The second survey administered after the class had reconstructed the Chivas Regal ad in the alternative signification exercise was done to determine any change in their reading of the text. The students' answers in the two surveys were compared and showed that the students attained the second order of signification in the process of reading the text. However, there was little change in their perception of the use of woman in the ad even after the alternative signification exercise. This could be due to the strength of their gender attitudes prior to the study. The results also showed that the students failed to reach the third order of signification without teacher-led discussion of the implications of alternative signification.
Keywords: Reading